Adipose tissue-derived microRNA-450a-5p induces type 2 diabetes mellitus by downregulating DUSP10 - Jiaojiao Zhu; Yanting Hou; Wei Yu; Jingzhou Wang; Xiaolong Chu; Xueting Zhang; Huai Pang; Dingling Ma; Yihan Tang; Menghuan Li; Chenggang Yuan; Jianxin Xie; et al. (Molecular Biomedicine)
Abstract Type 2 diabetes mellitus (T2DM) has rapidly increased worldwide, emerging as the fifth leading cause of death. The treatment of T2DM is challenging due to the side effects of oral hypoglycemic drugs and the limited efficacy of long-term insulin therapy, which can lead to insulin resistance (IR). Consequently, there is significant in discovering new drugs that have minimal side effects and a pronounced hypoglycemic effect. In obesity, microRNA levels have been implicated in glucose metabolism disorders and T2DM, although many aspects remain unresolved. Here, we confirmed that visceral adipose tissue and serum microRNA-450a-5p content increased under obesity and T2DM, and it was significantly positively associated with fasting blood glucose, triglycerides, cholesterol, low-density lipoproteins-cholesterol levels of the subjects. In high-fat diet (HFD)-induced obese mice, microRNA-450a-5p expression was increased in the serum, liver, and white adipose tissue. Moreover, the adipose Dicer-knockout mouse model was constructed to identify adipose tissue as the main source of microRNA-450a-5p. microRNA-450a-5p could inactivate the insulin signal pathway by targeting the inhibited Dual Specificity Phosphatase 10 (DUSP10) and inducing IR and glucose metabolism disorders in vitro cultured hepatocytes and adipocytes. Additionally, microRNA-450a-5p was found to regulate DUSP10 expression and insulin signaling activity, influencing glucose tolerance and insulin sensitivity across various models, including normal diet, HFD-induced obese, adipose tissue-specific microRNA-450a-5p-knockout, and db/db mice. Furthermore, gallic acid might play a potential role in inhibiting glucose levels by decreasing microRNA-450a-5p expression. Thus, microRNA-450a-5p emerges as an attractive therapeutic target for addressing obesity, IR, and T2DM.